The Historical, stylistic, analytical, and pedagogical aspects of Wolfgang Amadeus Mozart’s Piano Sonata in A Major K 331, Frédéric Chopin’s Ballade No. 1 in G Minor, Op. 23, and Claude Debussy’s Jardins sous la pluie - Seok, Beomseung (Kansas State University, 2024)
At my Master’s lecture recital held on March 30, 2024, I presented and performed three piano compositions spanning different stylistic periods. The repertoire comprised Wolfgang Amadeus Mozart’s Piano Sonata in A Major K 331, Frédéric Chopin’s Ballade No. 1 in G Minor, op. 23, and Claude Debussy’s “Jardins sous la pluie” from Estampes. This lecture encompassed comprehensive discussions on each composer’s biographical background, as well as the historical, stylistic, analytical, and pedagogical dimensions of the selected pieces.
Keywords: Mozart Piano Sonata in A Major K 331; Chopin Ballade No. 1 in G Minor, op. 23; Debussy Jardins sous la pluie